Generation and biochemical characterization of glycoPEGylated factor VIIa derivatives - Stennicke, Henning R.; Østergaard, Henrik; Bayer, Robert J.; Kalo, Matt S.; Kinealy, Kyle; Holm, Pernille K.; Sørensen, Brit B.; Zopf, David; Bjørn, Søren E. (Thrombosis and Haemostasis, 2008)
Prophylaxis with 2–4 times weekly dosing of factor (F)VIII or FIX is established as an efficacious and safe treatment in haemophilia. Although prophylaxis is not readily available for the inhibitor patient,recent studies have demonstrated a reduction in bleeding episodes in inhibitor patients treated with daily infusions of FVIIa. In order to develop a treatment option comparable to prophylaxis with FVIII or FIX we looked to PEGylation which is an established method for prolonging the circulatory half-life of proteins. However, due to the numerous interactions of FVIIa with the cell surface,TF,FIX and FX there are limited options for unspecific chemical modification of FVIIa without loss of activity. Consequently, we explored the GlycoPEGylation™ technology for selective PEGylation of the two N-glycans in the FVIIa light chain and protease domain to generate seven specifically modified derivatives with PEG groups ranging from 2 to 40 kDa. These derivatives were evaluated in vitro for their ability to interact with small synthetic substrates as well as key molecules relevant to function in the coagulation pathway. The results demonstrate that modification of FVIIa using glycoPEGylation has only a very limited effect on the hydrolysis S-2288 and FX activation. However, the modification does to some extend alter the ability of FVIIa to interact with TF and more importantly, reduces the rate of ATIII inhibition by up to 50% which could allow for an extended active half-life in circulation.
Keywords: Long-acting; PEG; coagulation; serine protease; factor VIIa; prophylaxis